Excitement Processes Norbert Elias's unpublished works on sports, leisure, body, culture (Springer Fachmedien Wiesbaden : VS, 2018)
The book focuses on major aspects of Norbert Elias's social theory through research on supposed "minor" topics, such as manners, sports, leisure and cultural practices. While many of his publications became essential for scholars in the different disciplines concerned, the development of the figurational approach towards these fields was not always completed. The edited volume picks up some lose ends by including archive manuscripts by Elias on the genesis of sport, developments of cultural practices, and the sociology of the body, which are published here for the very first time. Based on critical reviews of these texts, international experts show how the new material adds up to Elias's oeuvre and how it can be fruitfully applied to current research. Contents Leisure and culture Sportisation and 'modernisation' Sport, violence and state formation Sociology of the body Target Groups Students and reseachers of sociology, social and cultural sciences, sports, and history The Editors Dr. Jan Haut is researcher and lecturer at the Department of Sports Sciences, Goethe University Frankfurt (Germany). Dr. Paddy Dolan is a senior lecturer in the Department of Social Sciences, Dublin Institute of Technology (Ireland). Dr. Dieter Reicher is associated professor at the University of Graz (Austria). Dr. Raúl Sánchez García is lecturer of Sociology of Sport at the Universidad Europea in Madrid (Spain).